The Influence of Epistemological Views and AI Technology Literacy on Teachers' Self-Efficacy in Carrying Out Lead-ership Tasks Study of SDN Penukal - Widiyanti, Elya; Aliya Shabirah Budiman; Darwin Effendi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the influence of epistemological views and artificial intelligence (AI) technology literacy on teacher self-efficacy in carrying out leadership tasks in elementary schools. The background of this study is based on the challenges of digital education transformation in the Penukal District, Penukal Abab Lematang Ilir (PALI) Regency, which requires teachers to have adaptive and technology-based leadership skills. This study uses a quantitative approach with a causal associative design and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis technique. The study population involved all 30 elementary school teachers in Penukal District, with a total sampling technique. The results showed that both epistemological views and AI technology literacy had a positive and significant effect on teacher self-efficacy. AI technology literacy made a greater contribution, indicating that understanding and skills in AI technology substantially increased teachers' confidence in leading change. These findings recommend the importance of teacher training programs that integrate strengthening epistemological thinking and digital skills to support sustainable educational transformation.